EFFECT OF FORTIFICATION BLUE GREEN ALGAE (Spirulina) ON MACARONI catfish (Pangasius hyppophthalmus) ACCEPTANCE OF CONSUMER - Erwinsyah '; Suparmi '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aimed to determine the effect of fortification blue green algae (Spirulina) on macaroni catfish (Pangasius hyphophthalmus) on consumer acceptance. The method used is the experimental method, namely the experiment of making macaroni catfish with a number of different Spirulina. This study used a completely randomized design with 4 treatments and 3 replications. The treatments that M0 (without Spirulina), M1 (Spirulina 5 grams), M2 (Spirulina 10 grams), M3 (Spirulina 15 grams). The results of this study showed the addition of Spirulina for all treatments have acceptance of consumer ranged from 59.37% -83.75% where the treatment M0 (59.37), M1 (71.87), M2 (83.75), M3 (67.12). The best macaroni is that with the addition of M2 (Spirulina 10 grams) which has a 83.75% acceptance level with the characteristics of a light green color, the aroma of fish and Spirulina little felt, and compact texture. Treatment of M2 has a water content of 9.54%; protein of 10.51%; fat of 1.77% and 63.52% rehydration capacity.Keywords: Spirulina, Macaroni, Fortification